Medical and psychological support for military personnel with chronic pain in rehabilitation centers - Nikolaieva, Oleksandra (Psychosomatic Medicine and General Practice, 2025)
Military operations in Ukraine are causing an unprecedented increase in the number of gunshot wounds, which account for 47% of all traumatic injuries. Multilevel damage to anatomical structures in high-energy trauma in 68.5% of cases leads to the formation of chronic pain syndrome with concomitant psycho-emotional and cognitive disorders, creating a pathological circle of mutual reinforcement of manifestations. This problem is gaining not only medical, but also socio-economic importance for the development of the country.